2015
DOI: 10.1159/000441342
|View full text |Cite
|
Sign up to set email alerts
|

Growth in Boys with 45,X/46,XY Mosaicism: Effect of Growth Hormone Treatment on Statural Growth

Abstract: 45,X/46,XY mosaicism is a rare sex chromosome disorder of sex development. Short stature is a main feature of boys with this condition. Different causes likely contribute to growth impairment. Growth hormone (GH) has been administered to treat short stature in boys with 45,X/46,XY mosaicism, but conflicting data are available. Here, spontaneous growth patterns as well as short- and long-term follow-up studies during GH therapy in these patients are reviewed. Short- and mid-term data showed an improvement of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…For example, no data are available on the prevalence and extent of catch-up growth in children with atypical genitalia who were born small for gestational age. In individuals with 45X/46XY karyotypes, growth hormone treatment has variable effects and may need to be optimised (36,37). Age at start of puberty induction and dosing of sex steroids may affect the growth pattern and body proportions (38).…”
Section: Anthropometric Data Body Composition and Bone Healthmentioning
confidence: 99%
“…For example, no data are available on the prevalence and extent of catch-up growth in children with atypical genitalia who were born small for gestational age. In individuals with 45X/46XY karyotypes, growth hormone treatment has variable effects and may need to be optimised (36,37). Age at start of puberty induction and dosing of sex steroids may affect the growth pattern and body proportions (38).…”
Section: Anthropometric Data Body Composition and Bone Healthmentioning
confidence: 99%
“…The wide spectrum of phenotypes in these patients is also reflected in health outcomes such as growth, gonadal function, risk of gonadal neoplasia and comorbidities that are all reported with varying incidences and severities both within the same centers and between centers (5,7,10,(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…Lindhardt et al 3 reported increasing HSDS after 1 year of GH therapy. But, the results of long‐term studies are conflicting 4,5,17,18 In our cohort, 10 patients were treated with GH, and 8 were female. AHSDS was similar in GH‐treated and GH‐untreated groups.…”
Section: Discussionmentioning
confidence: 85%